Communication Contestation Between Genshin Impact Enthusiasts and Sonic Frontier on Twitter Account @nikolavalent - Larasati, Catharina Putri; Fensi, Fabianus (UNIVERSITAS PAKUAN, 2022)
In the current digital era, fan communities of video games wield significant influence within the entertainment industry. This phenomenon encompasses not only positive support but also frequently involves intense communication contestation among fans of various games. One noteworthy case that has garnered attention is the rivalry between Genshin Impact and Sonic Frontier enthusiasts. Verbal conflicts between these two fan groups have evolved into heated debates across various social media platforms, online forums, and social networks. This research adopts a qualitative approach to explore and analyze the communication contestation between Genshin Impact and Sonic Frontier fans. We employ two primary theoretical frameworks: Grice's conversational maxims analysis and Sara Mills' critical discourse analysis model to gain a deeper understanding of the dynamics of these conversations and their implications on the identities and self-perceptions of the fans. Our research findings reveal that contestation escalates when violations of the maxims of attitude are present in the conversations. Furthermore, the study also identifies attempts to construct a social narrative suggesting that fans of both games have deviant sexual interests. These findings reflect the complexity of online communication within video game fan communities and its relevance in understanding shifts in identity and social constructions in the digital era.